Differences in frontal and limbic brain activation in a small sample of monozygotic twin pairs discordant for severe stressful life events - Detre A. Godinez; Kateri McRae; Jessica R. Andrews-Hanna; Harry Smolker; Marie T. Banich (Neurobiology of Stress, 2016)
Monozygotic twin pairs provide a valuable opportunity to control for genetic and shared environmental influences while studying the effects of nonshared environmental influences. The question we address with this design is whether monozygotic twins selected for discordance in exposure to severe stressful life events during development (before age 18) demonstrate differences in brain activation during performance of an emotional word-face Stroop task. In this study, functional magnetic resonance imaging was used to assess brain activation in eighteen young adult twins who were discordant in exposure to severe stress such that one twin had two or more severe events compared to their control co-twin who had no severe events. Twins who experienced higher levels of stress during development, compared to their control co-twins with lower stress, exhibited significant clusters of greater activation in the ventrolateral and medial prefrontal cortex, basal ganglia, and limbic regions. The control co-twins showed only the more typical recruitment of frontoparietal regions thought to be important for executive control of attention and maintenance of task goals. Behavioral performance was not significantly different between twins within pairs, suggesting the twins with stress recruited additional neural resources associated with affective processing and updating working memory when performing at the same level. This study provides a powerful glimpse at the potential effects of stress during development while accounting for shared genetic and environmental influences.